Social identity and cortisol responses to competition in male competitive youth hockey players - Carré, J.; Geniole, S.; Martin, L. J.; Herbison, J. D.; Slatcher, R.; Boardley, I.; Benson, A.; McLaren, C.; Sutcliffe, J.; Côté, J.; Bruner, M. W. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Cortisol is a steroid hormone synthesized and secreted by the adrenal glands during experiences of physical and psycho-social stress. Cortisol levels have been found to rise sharply within the context of competitive interactions, yet with noticeable variability among athletes (Casto & Edwards, 2016). Here, we examined whether the degree to which one identifies with one`s teammates (known as social identity) and competition outcome explain some of the variability in neuroendocrine reactivity patterns. One hundred and thirty-four male hockey players (Mage = 12.39, range = 10-14 years) from 9 hockey teams completed a sport specific social identity questionnaire (Bruner & Benson, 2018) and provided saliva samples before and after each of their 3 competitive ice hockey tournament games. Cortisol concentrations were assayed using commercially-available enzyme immunoassay kits. Multi-level analyses were performed to examine the extent to which variability in social identity (and its individual dimensions: ingroup ties, ingroup affect, cognitive centrality) and/or competition outcome predicted variability in cortisol reactivity patterns. Preliminary analyses revealed that competition outcome modulated cortisol responses, whereby cortisol levels were higher after defeats relative to victories. Moreover, athletes who felt increased positive emotions toward their teams (i.e., ingroup affect) demonstrated a more robust increase in cortisol levels relative to athletes who reported less positive feelings associated with teammembership. The extent to which stronger cortisol responses to competitive interactions play a role in modulating athletic performance and/or important group related emergent states (e.g., cohesion) after competitive interactions will be discussed.